Study protocol for assessing the effectiveness, implementation fidelity and uptake of attachment & child health (ATTACH™) Online: helping children vulnerable to early adversity - Nicole Letourneau; Lubna Anis; Cui Cui; Ian D. Graham; Kharah Ross; Kendra Nixon; Jan Reimer; Miranda Pilipchuk; Emily Wang; Simone Lalonde; Suzanna Varro; Maria Jose Santana; et al. (BMC Pediatrics)
Abstract Background Exposure to early childhood adversities, such as family violence, parental depression, or low-income, undermine parent–child relationship quality and attachment leading to developmental and mental health problems in children. Addressing impacts of early childhood adversity can promote children’s development, giving them the best start in life. Parental reflective function (RF), or parents' ability to understand their own and children's mental states, can strengthen parent–child relationships and attachment and buffer the negative effects of early adversity. We developed and tested ATTACH™ (Attachment and Child Health), an effective RF intervention program for parents and their preschool-aged children at-risk from early adversity. Pilot studies revealed significantly positive impacts of ATTACH™ from in-person (n = 91 observations of 64 dyads) and online (n = 10 dyads) implementation. The two objectives of this study are to evaluate: (1) effectiveness, and (2) implementation fidelity and uptake of ATTACH™ Online in community agencies serving at-risk families in Alberta, Canada. Our primary hypothesis is ATTACH™ Online improves children’s development. Secondary hypotheses examine whether ATTACH™ Online improves children’s mental health, parent–child relationships, and parental RF. Methods We will conduct an effectiveness-implementation hybrid (EIH) type 2 study. Effectiveness will be examined with a quasi-experimental design while implementation will be examined via descriptive quantitative and qualitative methods informed by Normalization Process Theory (NPT). Effectiveness outcomes examine children’s development and mental health, parent–child relationships, and RF, measured before, after, and 3 months post-intervention. Implementation outcomes include fidelity and uptake of ATTACH™ Online, assessed via tailored tools and qualitative interviews using NPT, with parents, health care professionals, and administrators from agencies. Power analysis revealed recruitment of 100 families with newborn to 36-month-old children are sufficient to test the primary hypothesis on 80 complete data sets. Data saturation will be employed to determine final sample size for the qualitative component, with an anticipated maximum of 20 interviews per group (parents, heath care professionals, administrators). Discussion This study will: (1) determine effectiveness of ATTACH™ Online and (2) understand mechanisms that promote implementation fidelity and uptake of ATTACH™ Online. Findings will be useful for planning spread and scale of an effective online program poised to reduce health and social inequities affecting vulnerable families. Trial registration Name of registry: https://clinicaltrials.gov/ . Registration number: NCT05994027. Date of registration: July 22, 2023. Protocol version Version 1.